High mortality risk among women with acromegaly still persists - Găloiu, Simona; Toma, Iustin-Daniel; Tănasie, Denisa Isabella; Bărbulescu, Andreea; Baciu, Ionela; Niculescu, Dan Alexandru; Trifănescu, Raluca Alexandra; Căpăţînă, Cristina; Radian, Şerban; Poiană, Cătălina (Frontiers in Endocrinology, 2024)
Introduction. The mortality ratio in patients with acromegaly has improved over the last few decades. We aimed to determine the mortality rate and correlated factors in patients with acromegaly before and after the introduction of national protocols for treatment. In addition, we determined whether there are sex-related differences in mortality of patients with acromegaly.Methods. This observational retrospective study included 399 consecutive patients with acromegaly between January 2001-December 2022. Paraclinical data included random growth hormone (GH) and insulin-like growth factor-I (IGF1) levels, maximal pituitary tumor diameter at diagnosis, first visit, and last evaluation. Standardized mortality ratio (SMR) was calculated by dividing the observed and expected mortality rates. Cox regression analysis revealed the independent factors associated with mortality.Results. At the last visit, 31.07% (124) of patients were cured, 22.05% (88) had controlled acromegaly with medication, and 45.31% (181) had not controlled acromegaly. During follow-up (13.03 ± 5.65 years, 5216.62 person-years), 89 patients died (0.017%), resulting in an SMR of 1.18 [95% CI 0.95-1.45]. The independent factors associated with mortality were the last IGF1 level/last random GH level, absence of surgery, gonadotropin deficiency, and age. Patients with normal IGF1 after treatment showed an SMR of 0.71, whereas patients with IGF1 ratio > 1 showed SMR=1.51.